Analysis of Natural Destruction in the Short Story “Sungai Kami” by Ghina Fadhilah: An Ecocritical Study of Greg Garrard - Annisa Luluk Firdausie (Jurnal Pendidikan dan Sastra Inggris, 2024)
The short story “Sungai Kita” by Ghina Fadhilah tells the story of the character Aku and her family who come from a village family and depend for their lives on the clarity of the water of their village river. Through rivers that have clean water, it symbolizes that the community is very close to nature. The problem encountered in this research is how the ecological representation of the area is and what the relationship between humans and nature is in the short story. The theory used is ecocritical theory and uses a qualitative method with a discourse approach and Greg Garrad’s Ecocritical Studies. The main data for this research is a short story by Ghina Fadhilah entitled “Sungai Kami”. The ecological data contained in the short story is the result of a literary study which is then connected to other written texts. Based on critical ecological analysis, it can be concluded that the short story “Sungai Kami” not only depicts the closeness of humans to nature but also shows the connection between nature and the philosophy of life.